2022
DOI: 10.1101/2022.12.27.521952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SCIP: a self-paced, community-based summer coding program creates community and increases coding confidence, lessons learned from the pandemic

Abstract: In 2020, many students lost summer opportunities due to the COVID-19 pandemic. We wanted to offer students an opportunity to learn computational skills and be part of a community while stuck at home. Because the pandemic created an unexpected research and academic situation, it was unclear how to best support students to learn and build community online. We used lessons learned from literature and our own experience to design, run and test an online program for students called the Science Coding Immersion Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In 2021 and 2022, we let students at San Francisco State University in the Biology Master's program and in the summer SCIP program [15] work through the module. We found that our students had limited prior knowledge of machine learning (see Figure 2, panel A), but after doing the tutorial, 71.8% of the students were interested in learning more (the remaining students indicated they were "maybe" interested in learning more, and one student out of 78 indicated they were not interested in learning more).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021 and 2022, we let students at San Francisco State University in the Biology Master's program and in the summer SCIP program [15] work through the module. We found that our students had limited prior knowledge of machine learning (see Figure 2, panel A), but after doing the tutorial, 71.8% of the students were interested in learning more (the remaining students indicated they were "maybe" interested in learning more, and one student out of 78 indicated they were not interested in learning more).…”
Section: Resultsmentioning
confidence: 99%
“…We programmed our tutorial in Python, which is one of the most popular coding languages [12,13]. It is considered a good language to learn for beginners because of its relative simplicity [14]. The tutorial does not require specialized knowledge in any particular biological concept and is designed to be a friendly introduction to the decision tree algorithm for students with no prior coding or machine learning knowledge.…”
Section: Introductionmentioning
confidence: 99%